Electrolyte, electrochemical device and electronic device
By using the electrolyte of the compound of formula I that can preferentially oxidize and decompose and form a stable interface protective film in lithium-ion batteries, the problem of insufficient stability and safety of lithium-ion batteries at high temperatures is solved, and higher cycle stability and high-temperature storage performance are achieved.
Patent Information
- Application Number
- CN202180006145.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-03-22
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2041-03-22
AI Technical Summary
Existing lithium-ion batteries have insufficient stability and safety at high temperatures, and there are problems such as catalytic decomposition of electrolytes and high interface impedance.
An electrolyte including a compound of formula I is used, which can preferentially oxidize and decompose, form a dense CEI film on the surface of the positive electrode, reduce the contact between the electrolyte and the positive electrode material, inhibit the catalytic decomposition of the electrolyte, and form a stable protective film on the surface of the negative electrode to capture trace amounts of water and HF.
By forming a stable interface protective film, the cycle stability and high-temperature storage performance of lithium-ion batteries are significantly improved, the inflation of the electrochemical device is suppressed, and the interface impedance is reduced.
Smart Images

Figure CN114667624B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemistry, and in particular to an electrolyte, an electrochemical device and an electronic device. Background Art
[0002] Electrolyte is an important component of electrochemical devices (such as lithium-ion batteries), and plays a vital role in the specific capacity, charge and discharge efficiency, cycle stability, rate performance, operating temperature range, and safety performance of electrochemical devices. With the widespread application of lithium-ion batteries, people have put forward higher requirements for their stability and safety at high temperatures. Summary of the invention
[0003] In view of this, the purpose of the present application is to provide an electrolyte, an electrochemical device and an electronic device to solve the problems existing in the prior art.
[0004] In the embodiment of the present application, an electrolyte is provided, comprising: a compound of formula I;
[0005]
[0006] wherein A is selected from -C(=O)- or -S(=O)2-; R1 is selected from substituted or unsubstituted C1 to C 20 alkyl or heteroalkyl, substituted or unsubstituted C1 to C 20 alkoxy or heteroalkoxy, substituted or unsubstituted C2 to C 20 alkenyl or heteroalkenyl, substituted or unsubstituted C2 to C 20 alkynyl or heteroalkynyl, substituted or unsubstituted C6 to C 20 aryl or heteroaryl, substituted or unsubstituted C3 to C 20 alicyclic hydrocarbon group, substituted or unsubstituted C2 to C 20 Any of the heterocyclic groups, wherein, when substituted, the substituent comprises halogen; R2, R3 and R4 are each independently selected from hydrogen, halogen, substituted or unsubstituted C1 to C 20 alkyl or heteroalkyl, substituted or unsubstituted C1 to C 20 alkoxy or heteroalkoxy, substituted or unsubstituted C2 to C 20 alkenyl or heteroalkenyl, substituted or unsubstituted C2 to C 20 alkynyl or heteroalkynyl, substituted or unsubstituted C6 to C 20 aryl or heteroaryl, substituted or unsubstituted C3 to C 20 alicyclic hydrocarbon group, substituted or unsubstituted C2 to C 20Any one of the heterocyclic groups, wherein, when substituted, the substituent comprises halogen; when containing heteroatoms, the heteroatoms comprise at least one of O, N, P, S, Si or B; n is selected from 1 or 2; m is selected from 0 or 1; m+n=2.
[0007] In some embodiments, R1 is selected from substituted or unsubstituted C1 to C 10 alkyl or heteroalkyl, substituted or unsubstituted C1 to C 10 alkoxy or heteroalkoxy, substituted or unsubstituted C2 to C 10 alkenyl or heteroalkenyl, substituted or unsubstituted C2 to C 10 alkynyl or heteroalkynyl, substituted or unsubstituted C6 to C 10 aryl or heteroaryl, substituted or unsubstituted C3 to C 10 alicyclic hydrocarbon group, substituted or unsubstituted C2 to C 10 Any one of the heterocyclic groups; R2, R3 and R4 are each independently selected from hydrogen, halogen, substituted or unsubstituted C1 to C 10 alkyl or heteroalkyl, substituted or unsubstituted C1 to C 10 alkoxy or heteroalkoxy, substituted or unsubstituted C2 to C 10 alkenyl or heteroalkenyl, substituted or unsubstituted C2 to C 10 alkynyl or heteroalkynyl, substituted or unsubstituted C6 to C 10 aryl or heteroaryl, substituted or unsubstituted C3 to C 10 alicyclic hydrocarbon group, substituted or unsubstituted C2 to C 10 Any of the heterocyclic groups.
[0008] In some embodiments, the compound of formula I includes at least one of the following compounds:
[0009]
[0010]
[0011] In some embodiments, based on the mass of the electrolyte, the mass percentage of the compound of formula I is 0.01% to 5%. In some embodiments, the electrolyte further includes a sulfur-oxygen double bond-containing compound, and the sulfur-oxygen double bond-containing compound includes at least one of the compounds represented by formula (II-A) and formula (II-B);
[0012]
[0013] In formula (II-A) and formula (II-B), R 21 , R 22 , R 23 and R24 are each independently selected from substituted or unsubstituted C1 to C5 alkyl, substituted or unsubstituted C2 to C 10 alkenyl, substituted or unsubstituted C2 to C 10 Alkynyl, substituted or unsubstituted C3 to C 10 Alicyclic hydrocarbon group, substituted or unsubstituted C6 to C 10 any one of an aryl group, a substituted or unsubstituted C1 to C6 heteroatom-containing group, and, when substituted, the substituent includes at least one of a halogen and a heteroatom-containing group, and the heteroatom includes at least one of O, S, P, N, Si or B, wherein R 21 and R 22 They can be bonded to form a ring structure, R 23 and R 24 They can be bonded to form a ring structure.
[0014] In some embodiments, the sulfur-oxygen double bond-containing compound includes at least one of the compounds represented by formula (II-1) to formula (II-20);
[0015]
[0016] In some embodiments, the mass percentage of the sulfur-oxygen double bond compound is 0.01% to 5% based on the mass of the electrolyte. In some embodiments, the electrolyte further includes a polynitrile compound; the polynitrile compound includes at least one of the compounds represented by formula III;
[0017]
[0018] In Formula III, R 31 , R 32 , R 33 , R 34 are each independently selected from hydrogen, substituted or unsubstituted C1 to C 10 Alkyl, substituted or unsubstituted -(CH2) a -CN, substituted or unsubstituted -(CH2) b -O-(CH2) c -CN, substituted or unsubstituted -(CH2) d -CH=CH-(CH2) k -CN, substituted or unsubstituted Substituted or unsubstituted Any one of substituted or unsubstituted alkoxycarbonyl groups, wherein a, b, c, d, e, f, g, h, i, j, k are each independently selected from integers from 0 to 10, and, when substituted, the substituent comprises at least one of halogen; x is selected from an integer from 0 to 3, and, when n is selected from an integer from 1 to 3, R 31 , R 32 , R 33 , R 34 At least two of them are groups containing cyano groups, when n is selected from 0, R 32 and R 34 All contain at least a cyano group.
[0019] In some embodiments, the polynitrile compound includes at least one of the compounds represented by Formula III-1 to Formula III-18;
[0020]
[0021]
[0022] In some embodiments, based on the mass of the electrolyte, the mass percentage of the polynitrile compound is 0.5% to 10%.
[0023] In some embodiments, the electrolyte further comprises a cyclic carbonate compound; the cyclic carbonate compound comprises at least one of the compounds represented by formula IV-A or IV-B;
[0024]
[0025] R 41 and R 42 Each is independently selected from any one of hydrogen, halogen, C1 to C5 alkyl group which may be substituted with or without fluorine, and C2 to C5 alkenyl group; R 43 , R 44 are each independently selected from any one of hydrogen, halogen and fluorine-substituted C1 to C5 alkyl, C2 to C5 alkenyl, provided that R 43 and R 44 At least one of them is selected from halogen, fluorine-substituted C1 to C5 alkyl or C2 to C5 alkenyl.
[0026] In some embodiments, the cyclic carbonate compound includes at least one of the compounds represented by Formula IV-1 to Formula IV-7;
[0027]
[0028] In some embodiments, based on the mass of the electrolyte, the mass percentage of the cyclic carbonate compound is 0.01% to 5%.
[0029] The present application also provides an electrochemical device, comprising: the above-mentioned electrolyte of the present application.
[0030] The present application also provides an electronic device, comprising the electrochemical device of the present application.
[0031] The embodiment of the present application provides an electrolyte, in which the compound of formula I in the electrolyte can be preferentially oxidized and decomposed to form a dense and stable CEI (cathode electrolyte interphase) film on the surface of the positive electrode, reducing the contact between the electrolyte and the positive electrode material, thereby inhibiting the catalytic decomposition of the electrolyte and reducing the interface impedance. At the same time, it can be reduced to form a film on the surface of the negative electrode, reducing the reduction and decomposition of the electrolyte at the negative electrode. The compound of formula I can capture trace water and hydrofluoric acid in the electrolyte, and at the same time form a stable protective film at the positive and negative electrodes, which can effectively improve the cycle stability and inhibit the flatulence of the electrochemical device during high temperature cycling and storage. DETAILED DESCRIPTION
[0032] The embodiments of the present application will be described in more detail below. Although some embodiments of the present application are shown, it should be understood that the application can be realized by various forms, and should not be construed as being limited to the embodiments set forth herein, but these embodiments are provided in order to more thoroughly and completely understand the application. The following embodiments can make those skilled in the art understand the application more comprehensively, but do not limit the application in any way. The scheme provided by the embodiments of the present application will be described in detail below.
[0033] The present application proposes a non-aqueous electrolyte solution that improves the high-temperature cycle performance of an electrochemical device, suppresses flatulence, and reduces impedance.
[0034] In some embodiments of the present application, an electrolyte is provided, comprising: a compound of formula I;
[0035]
[0036] wherein A is selected from -C(=O)- or -S(=O)2-; R1 is selected from substituted or unsubstituted C1 to C 20 alkyl or heteroalkyl, substituted or unsubstituted C1 to C 20 alkoxy or heteroalkoxy, substituted or unsubstituted C2 to C 20 alkenyl or heteroalkenyl, substituted or unsubstituted C2 to C 20 alkynyl or heteroalkynyl, substituted or unsubstituted C6 to C 20 aryl or heteroaryl, substituted or unsubstituted C3 to C 20 alicyclic hydrocarbon group, substituted or unsubstituted C2 to C 20Any of the heterocyclic groups, wherein, when substituted, the substituent comprises halogen; R2, R3 and R4 are each independently selected from hydrogen, halogen, substituted or unsubstituted C1 to C 20 alkyl or heteroalkyl, substituted or unsubstituted C1 to C 20 alkoxy or heteroalkoxy, substituted or unsubstituted C2 to C 20 alkenyl or heteroalkenyl, substituted or unsubstituted C2 to C 20 alkynyl or heteroalkynyl, substituted or unsubstituted C6 to C 20 aryl or heteroaryl, substituted or unsubstituted C3 to C 20 alicyclic hydrocarbon group, substituted or unsubstituted C2 to C 20 Any one of the heterocyclic groups, wherein, when substituted, the substituent comprises halogen; when containing heteroatoms, the heteroatoms comprise at least one of O, N, P, S, Si or B; n is selected from 1 or 2; m is selected from 0 or 1; m+n=2.
[0037] The electrolyte proposed in some embodiments of the present application can form a stable interface protection on the positive electrode surface and the negative electrode surface of the electrochemical device, thereby significantly improving the cycle life and high temperature storage performance of the electrochemical device using the electrolyte. When the electrochemical device is charged for the first time, the compound of formula I can preferentially oxidize and decompose to form a dense and stable CEI film on the positive electrode surface, reduce the contact between the electrolyte and the positive electrode material, thereby inhibiting the catalytic decomposition of the electrolyte and reducing the interface impedance. At the same time, it can be reduced to form a film on the negative electrode surface, reducing the reduction and decomposition of the electrolyte at the negative electrode. The compound of formula I can capture trace water and HF in the electrolyte, and at the same time form a stable protective film on the positive and negative electrodes. During high temperature cycling and storage, it can effectively improve the cycle stability and inhibit the flatulence of the electrochemical device.
[0038] In some embodiments of the present application, R1 is selected from substituted or unsubstituted C1 to C 10 alkyl or heteroalkyl, substituted or unsubstituted C1 to C 10 alkoxy or heteroalkoxy, substituted or unsubstituted C2 to C 10 alkenyl or heteroalkenyl, substituted or unsubstituted C2 to C 10 alkynyl or heteroalkynyl, substituted or unsubstituted C6 to C 10 aryl or heteroaryl, substituted or unsubstituted C3 to C 10 alicyclic hydrocarbon group, substituted or unsubstituted C2 to C 10 Any one of the heterocyclic groups; R2, R3 and R4 are each independently selected from hydrogen, halogen, substituted or unsubstituted C1 to C 10 alkyl or heteroalkyl, substituted or unsubstituted C1 to C 10alkoxy or heteroalkoxy, substituted or unsubstituted C2 to C 10 alkenyl or heteroalkenyl, substituted or unsubstituted C2 to C 10 alkynyl or heteroalkynyl, substituted or unsubstituted C6 to C 10 aryl or heteroaryl, substituted or unsubstituted C3 to C 10 alicyclic hydrocarbon group, substituted or unsubstituted C2 to C 10 Any of the heterocyclic groups.
[0039] In some embodiments of the present application, the compound of formula I includes at least one of the following compounds:
[0040]
[0041]
[0042] In some embodiments of the present application, based on the mass of the electrolyte, the mass percentage of the compound of formula I is 0.01% to 5%. In some embodiments, when the mass percentage of the compound of formula I is less than 0.01%, the improvement effect may not be obvious due to too little content, and when the mass percentage of the compound of formula I is greater than 5%, the ionic conductivity of the electrolyte may be reduced.
[0043] In some embodiments of the present application, the electrolyte further comprises a sulfur-oxygen double bond-containing compound, and the sulfur-oxygen double bond-containing compound comprises at least one of the compounds represented by formula (II-A) and formula (II-B);
[0044]
[0045] In formula (II-A) and formula (II-B), R 21 , R 22 , R 23 and R 24 are each independently selected from substituted or unsubstituted C1 to C5 alkyl, substituted or unsubstituted C2 to C 10 alkenyl, substituted or unsubstituted C2 to C 10 Alkynyl, substituted or unsubstituted C3 to C 10 Alicyclic hydrocarbon group, substituted or unsubstituted C6 to C 10 any one of an aryl group, a substituted or unsubstituted C1 to C6 heteroatom-containing group, and, when substituted, the substituent includes at least one of a halogen and a heteroatom-containing group, and the heteroatom includes at least one of O, S, P, N, Si or B, wherein R 21 and R 22 They can be bonded to form a ring structure, R 23 and R 24They can be bonded to form a ring structure. In some embodiments, the above-mentioned sulfur-oxygen double bond compound is added to the electrolyte to improve the high-temperature cycle and storage performance of the electrochemical device using the electrolyte. This is mainly because the sulfur-containing double bond compound can form an interface film rich in S elements, which can further improve the thermal stability and mechanical stability of the interface film. It can modify the SEI at the negative electrode to form a better interface protection film, alleviate the reaction of the electrolyte at the negative electrode, and thus further improve the cycle performance and high-temperature storage performance.
[0046] In some embodiments of the present application, the compound containing a sulfur-oxygen double bond includes at least one of the compounds represented by formula (II-1) to formula (II-20);
[0047]
[0048] In some embodiments of the present application, based on the mass of the electrolyte, the mass percentage of the sulfur-oxygen double bond compound is 0.01% to 5%. In some embodiments, too low a mass percentage of the sulfur-oxygen double bond compound results in an insignificant improvement effect, while too high a mass percentage increases costs.
[0049] In some embodiments of the present application, the electrolyte further comprises a polynitrile compound; the polynitrile compound comprises at least one of the compounds represented by formula III;
[0050]
[0051] In Formula III, R 31 , R 32 , R 33 , R 34 are each independently selected from hydrogen, substituted or unsubstituted C1 to C 10 Alkyl, substituted or unsubstituted -(CH2) a -CN, substituted or unsubstituted -(CH2) b -O-(CH2) c -CN, substituted or unsubstituted -(CH2) d -CH=CH-(CH2) k -CN, substituted or unsubstituted Substituted or unsubstituted Any one of substituted or unsubstituted alkoxycarbonyl groups, wherein a, b, c, d, e, f, g, h, i, j, k are each independently selected from integers from 0 to 10, and, when substituted, the substituent comprises at least one of halogen; x is selected from an integer from 0 to 3, and, when n is selected from an integer from 1 to 3, R 31 , R 32 , R 33 , R 34At least two of them are groups containing cyano groups, when n is selected from 0, R 32 and R 34 All contain at least a cyano group. In some embodiments, the introduction of polynitrile compounds can significantly improve the hot box performance and electrical properties. This is because polynitrile compounds can well separate the easily oxidized components in the electrolyte from the positive electrode surface, greatly reducing the oxidation of the positive electrode surface of the charged lithium ion battery to the electrolyte. The above-mentioned polynitrile compounds can form a synergistic effect with the formula I compound in the electrolyte, and can form a more stable SEI film, thereby further improving the high temperature cycle, high temperature storage and hot box performance of the electrochemical device.
[0052] In some embodiments of the present application, the polynitrile compound includes at least one of the compounds represented by Formula III-1 to Formula III-18;
[0053]
[0054]
[0055] In some embodiments, the mass percentage of the polynitrile compound is 0.5% to 10% based on the mass of the electrolyte. In some embodiments, too little mass percentage of the polynitrile compound may not significantly improve the effect, while too much mass percentage may affect the ionic conductivity of the electrolyte.
[0056] In some embodiments, the electrolyte further comprises a cyclic carbonate compound; the cyclic carbonate compound comprises at least one of the compounds represented by formula IV-A or IV-B;
[0057]
[0058] R 41 and R 42 Each is independently selected from any one of hydrogen, halogen, C1 to C5 alkyl group which may be substituted with or without fluorine, and C2 to C5 alkenyl group; R 43 , R 44 are each independently selected from any one of hydrogen, halogen and fluorine-substituted C1 to C5 alkyl, C2 to C5 alkenyl, provided that R 43 and R 44 At least one of them is selected from halogen, fluorine-substituted C1 to C5 alkyl or C2 to C5 alkenyl. In some embodiments, the cyclic carbonate compound in the electrolyte can form a more stable SEI film, thereby further improving the high temperature cycle and high temperature storage performance of the electrochemical device.
[0059] In some embodiments, the cyclic carbonate compound includes at least one of the compounds represented by Formula IV-1 to Formula IV-7;
[0060]
[0061] In some embodiments of the present application, the mass percentage of the cyclic carbonate compound is 0.01% to 5% based on the mass of the electrolyte. In some embodiments, when the mass percentage of the cyclic carbonate compound is too low, the improvement effect is not obvious, and when the mass percentage is too high, the ionic conductivity of the electrolyte may decrease.
[0062] In some embodiments of the present application, the electrolyte includes cyclic esters and chain esters, and the mass ratio of the cyclic esters to the chain esters is 1:9 to 7:3, wherein the cyclic ester is selected from at least one of ethylene carbonate (abbreviated as EC), propylene carbonate (abbreviated as PC), and γ-butyrolactone (abbreviated as BL); the chain ester is selected from at least one of dimethyl carbonate (abbreviated as DMC), diethyl carbonate (abbreviated as DEC), ethyl methyl carbonate (abbreviated as EMC), ethyl acetate (abbreviated as EA), methyl formate (abbreviated as MF), ethyl formate (abbreviated as MA), ethyl propionate (abbreviated as EP), propyl propionate (abbreviated as PP), methyl butyrate (abbreviated as MB), ethyl methyl fluorocarbonate, and ethyl fluoropropionate.
[0063] In some embodiments of the present application, the electrolyte contains a lithium salt, which may be at least one of an organic lithium salt or an inorganic lithium salt. In some embodiments of the present application, the lithium salt contains at least one of a fluorine element, a boron element, or a phosphorus element. In some embodiments, the lithium salt includes at least one of lithium hexafluorophosphate LiPF6, lithium bistrifluoromethanesulfonyl imide LiN(CF3SO2)2 (abbreviated as LiTFSI), lithium bis(fluorosulfonyl)imide Li(N(SO2F)2) (abbreviated as LiFSI), lithium bis(oxalatoborate) LiB(C2O4)2 (abbreviated as LiBOB), or lithium hexafluorocesium acid (LiCsF6), lithium perchlorate LiClO4, and lithium trifluoromethanesulfonate LiCF3SO3.
[0064] In some embodiments of the present application, the concentration of lithium salt is 0.5mol / L to 1.5mol / L. If the concentration of lithium salt is too low, the ionic conductivity of the electrolyte is low, which will affect the rate and cycle performance of the lithium-ion battery; if the concentration of lithium salt is too high, the viscosity of the electrolyte is too high, which will also affect the rate performance of the lithium-ion battery. Optionally, the concentration of lithium salt is 0.8mol / L to 1.2mol / L.
[0065] The present application also proposes an electrochemical device, comprising: a positive electrode, a negative electrode, a separator and any of the above electrolytes. The positive electrode of the above electrochemical device includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, and the positive electrode active material layer includes a positive electrode material. In some embodiments, the positive electrode material includes a positive electrode material capable of absorbing and releasing lithium (Li). Examples of positive electrode materials capable of absorbing / releasing lithium (Li) may include lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium iron manganese phosphate, lithium vanadium phosphate, lithium vanadium phosphate, lithium iron phosphate, lithium titanate and lithium-rich manganese-based materials. The positive electrode material can be selected from one or more of the following materials: LiCoO2, LiNiO2, LiMn2O4, LiCo 1-y M y O2、LiNi 1-y M y O2、LiMn 2-y M y O4、LiNi x Co y Mn z M 1-x-y-z O2, wherein M is selected from at least one of Fe, Co, Ni, Mn, Mg, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, V, and Ti, and 0≤y≤1, 0≤x≤1, 0≤z≤1, x+y+z≤1.
[0066] A conductive agent or a binder may be added to the positive active material layer of the electrochemical device. In some embodiments of the present application, the positive active material layer further comprises a carbon material, and the carbon material may include at least one of conductive carbon black, graphite, graphene, carbon nanotubes, carbon fibers or carbon black. The binder may include at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, a styrene-acrylate copolymer, a styrene-butadiene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinyl acetate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene.
[0067] In some embodiments, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector, the negative electrode active material layer includes a negative electrode material, and the negative electrode material may be made of, for example, a carbon material, a metal alloy, a lithium-containing oxide, and a silicon-containing material, etc. Among them, the carbon material is preferably graphite or a carbon material obtained by coating amorphous carbon compared to graphite on the surface of graphite.
[0068] In some embodiments, the isolation membrane includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. For example, polyethylene includes at least one selected from high-density polyethylene, low-density polyethylene or ultra-high molecular weight polyethylene. Especially polyethylene and polypropylene, they have a good effect on preventing short circuits and can improve the stability of the battery through the shutdown effect. In some embodiments, the isolation membrane surface may also include a porous layer, the porous layer is arranged on at least one surface of the isolation membrane, the porous layer includes inorganic particles and a binder, and the inorganic particles are selected from aluminum oxide (Al2O3), silicon oxide (SiO2), magnesium oxide (MgO), titanium oxide (TiO2), hafnium dioxide (HfO2), tin oxide (SnO2), cerium dioxide (CeO2), nickel oxide (NiO), zinc oxide (ZnO), calcium oxide (CaO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), silicon carbide (SiC), boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. At least one. The binder is selected from at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene. The porous layer on the surface of the separator can improve the heat resistance, oxidation resistance and electrolyte wetting performance of the separator, and enhance the adhesion between the separator and the pole piece.
[0069] The present application also proposes an electronic device, including any of the electrochemical devices described above. The electronic device of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, and a large household battery, etc.
[0070] In order to better illustrate the beneficial effects of the electrolyte proposed in the embodiments of the present application, the following will be described in combination with the embodiments and comparative examples. The difference between the embodiments and the comparative examples is only that the electrolytes used are different. In the embodiments and comparative examples, performance tests will be performed on lithium-ion batteries using different electrolytes to illustrate the influence of the electrolyte on the performance of the lithium-ion batteries.
[0071] Preparation of lithium-ion batteries
[0072] 1) Preparation of positive electrode: lithium manganese oxide LiMn2O4, Super P, and polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 96:2:2, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry, wherein the solid content of the positive electrode slurry is 72wt%; the positive electrode slurry is evenly coated on a 13μm aluminum foil; the aluminum foil is dried at 85°C, and then, after cold pressing, cutting, and slitting, it is dried under vacuum conditions at 85°C for 4h to obtain a positive electrode sheet.
[0073] 2) Preparation of negative electrode: artificial graphite, Super P, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) are mixed in a weight ratio of 96.4:1.5:0.5:1.6, deionized water is added, and negative electrode slurry is obtained under the action of a vacuum mixer, wherein the solid content of the negative electrode slurry is 54wt%; the negative electrode slurry is uniformly coated on the negative electrode current collector copper foil; the copper foil is dried at 85°C, and then after cold pressing, cutting, and slitting, it is dried under vacuum conditions at 120°C for 12h to obtain a negative electrode sheet.
[0074] 3) Preparation of electrolyte: In a dry argon atmosphere glove box, ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a mass ratio of EC:EMC:DEC=3:5:2, and then additives are added. After dissolving and stirring thoroughly, lithium salt LiPF6 is added and mixed to obtain an electrolyte. The concentration of LiPF6 is 1 mol / L. The difference between the various embodiments is that the additives used in the electrolyte are different. The specific types of additives and the mass percentages in the electrolyte are shown in Tables 1 to 4 below. The content of the additives is the mass percentage calculated based on the total mass of the electrolyte.
[0075] 4) Isolation membrane: A polyethylene (PE) porous polymer film is used as the isolation membrane.
[0076] 5) Preparation of lithium-ion batteries: stack the positive electrode sheet, the separator, and the negative electrode sheet in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wind them to obtain a bare cell; after welding the tabs, place the bare cell in an outer packaging aluminum-plastic film, inject the above-prepared electrolyte into the dried bare cell, and obtain a lithium-ion battery after vacuum packaging, standing, formation, shaping, capacity testing and other processes.
[0077] The testing process of lithium-ion batteries is as follows:
[0078] (1) Lithium-ion battery cycle performance test
[0079] Place the lithium-ion battery in a 45℃ constant temperature box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge the lithium-ion battery that has reached a constant temperature at a constant current of 0.5C to a voltage of 4.2V, then charge it at a constant voltage of 4.2V to a current of 0.05C, and then discharge it at a constant current of 1C to a voltage of 3.0V. This is a charge and discharge cycle. With the capacity of the first discharge as 100%, repeat the charge and discharge cycle for 500 times, stop the test, and record the cycle capacity retention rate as an indicator for evaluating the cycle performance of the lithium-ion battery.
[0080] Cycle capacity retention rate = discharge capacity at the 500th cycle / discharge capacity at the first cycle.
[0081] Measure the thickness of the battery and calculate the thickness expansion rate of the battery according to the following formula:
[0082] Thickness expansion rate = (battery thickness after cycle - battery thickness before cycle) / battery thickness before cycle × 100%
[0083] (2) 60℃ storage thickness expansion test
[0084] The lithium-ion battery was charged to 4.2V at 0.5C at 25°C, and then charged to 0.05C at a constant voltage at 4.2V. The thickness of the battery was measured with a micrometer and recorded as H. 11 ; Then place the battery in a 60℃ oven for 24 hours. After 24 hours, use a micrometer to measure and record the thickness of the battery at this time, which is recorded as H 12 . .
[0085] Thickness expansion rate of lithium-ion battery after storage at 60℃ for 24 hours (%) = (H 12 -H 11 ) / H 11 ×100%
[0086] (3) 140℃ hot box pass rate test
[0087] At 25°C, charge the lithium-ion battery at a constant current of 0.5C to 4.2V, and at a constant voltage of 4.2V to a current of 0.05C. Place the battery in a high temperature box, heat it to 140°C at a temperature rise rate of 5±2°C / min, and then keep it for 1h, and record the changes in the battery voltage, temperature, and temperature of the hot box. The battery passes the test if it does not catch fire, explode, or smoke. Test 10 batteries in each group and record the number of batteries that pass the test.
[0088] (4) 85℃ storage thickness expansion test
[0089] The lithium-ion battery was charged to 4.2V at 0.5C at 25°C, and then charged to 0.05C at a constant voltage at 4.2V. The thickness of the battery was measured with a micrometer and recorded as H.21 ; Then place the battery in an 85℃ oven for 24 hours. After 24 hours, use a micrometer to measure and record the thickness of the battery at this time, which is recorded as H 22 .
[0090] Thickness expansion ratio of lithium-ion battery after storage at 85℃ for 24 hours (%) = (H 22 -H 21 ) / H 21 ×100%
[0091] The additives used in Examples 1 to 19 and Comparative Examples 1 to 2, and the performance test results of lithium ion batteries are shown in Table 1. In Examples 1 to 19, the compound of formula I was added to the electrolyte, no additive was added to the electrolyte of Comparative Example 1, and phthalic anhydride was added to the electrolyte of Comparative Example 2.
[0092] Table 1
[0093]
[0094]
[0095] As shown in Table 1, the capacity retention rates of Examples 1 to 19 after 45°C cycling are higher than those of Comparative Examples 1 and 2, and the thickness expansion rates after 45°C cycling and the thickness expansion rates during 60°C storage are both lower than those of Comparative Examples 1 and 2. It can be seen that, compared with Comparative Example 1 in which no additive is used in the electrolyte, and Comparative Example 2 in which phthalic acid is used as an additive, the use of the compound of formula I can better improve the high-temperature cycling and high-temperature storage performances. This is mainly because the compound of formula I can adsorb trace water and HF in the electrolyte, thereby increasing the stability of the electrolyte; at the same time, it is easy to oxidize and form a dense protective film at the positive electrode, thereby reducing the damage of the electrolyte to the positive electrode; and during the first charge and discharge, it is preferentially reduced to form a film at the negative electrode, and the film is dense, thereby inhibiting the decomposition reaction of the electrolyte at the negative electrode.
[0096] It can be seen from Examples 1 to 12 that with the increase of the compound of formula I, the high temperature cycle performance and high temperature storage performance of the lithium ion battery first increase and then decrease. When the mass percentage of the compound of formula I is 1%, the performance is optimal. This is mainly because the addition amount can not only effectively stabilize the electrolyte, but also form excellent interface protection at the positive and negative electrodes at the same time. Too high a content of the compound of formula I leads to a large film formation impedance, which in turn leads to an increase in battery impedance and reduces battery performance; when the mass content of the compound of formula I is too low, it is not enough to form a good interface protection, and the effect of significantly improving battery performance cannot be achieved.
[0097] It can be seen from Examples 4, 16 to 19 that similar improvement effects can be achieved by using a single type of compound of Formula I and using multiple compounds of Formula I.
[0098] The additives used in Examples 4, 20 to 26 and Comparative Examples 1 and 3, and the performance test results of lithium ion batteries are shown in Table 2. The compound of formula I and the sulfur-oxygen double bond-containing compound were added to the electrolytes of Examples 20 to 26.
[0099] Table 2
[0100]
[0101] As shown in Table 2, by comparing the data of Examples 20 to 26, Example 4, and Comparative Examples 1 and 3, it can be seen that the 45°C cycle capacity retention rate of Examples 20 to 26 is higher than that of Example 4, Comparative Example 1, and Comparative Example 3, and the 45°C cycle thickness expansion rate and 60°C storage thickness expansion rate are lower than those of Example 4, Comparative Example 1, and Comparative Example 3. It can be seen that the addition of a sulfur-oxygen double bond compound to the electrolyte containing the compound of formula I can continue to improve the high-temperature cycle performance and high-temperature storage performance of the battery. This is mainly because the sulfur-containing double bond compound can form an interface film rich in S elements, which can further improve the thermal stability and mechanical stability of the interface film. Therefore, the combined use of the compound of formula I and the sulfur-oxygen double bond compound can further improve the cycle performance and high-temperature storage performance of lithium-ion batteries.
[0102] The additives used in Examples 4, 27 to 32 and Comparative Examples 1 and 4, and the performance test results of lithium ion batteries are shown in Table 3. In Examples 27 to 32, the compound of formula I and the polynitrile compound were added to the electrolyte.
[0103] Table 3
[0104]
[0105] As shown in Table 3, the 45°C cycle capacity retention rate and hot box pass rate of Examples 27 to 32 are higher than those of Example 4, Comparative Example 1 and Comparative Example 4, and the 85°C storage thickness expansion rate is lower than that of Example 4, Comparative Example 1 and Comparative Example 4. It can be seen that when the polynitrile compound is further added to the electrolyte, the 45°C cycle capacity retention rate of the lithium ion battery is improved, the 85°C storage thickness expansion rate is reduced, and the hot box pass rate is improved. It can be seen that the addition of the polynitrile compound improves the cycle performance, high temperature storage performance and safety performance of the lithium ion battery. This is because the polynitrile compound can form a synergistic effect with the compound of formula I in the electrolyte to form a more stable SEI film, thereby further improving the high temperature cycle, high temperature storage performance and hot box performance of the lithium ion battery.
[0106] The additives used in Examples 4, 33 to 37 and Comparative Examples 1 and 5, and the performance test results of lithium ion batteries are shown in Table 4. In Examples 33 to 37, the compound of formula I and the cyclic carbonate compound were added to the electrolyte.
[0107] Table 4
[0108]
[0109] As shown in Table 4, the 45°C cycle capacity retention rates of Examples 33 to 37 are higher than those of Example 4, Comparative Example 1 and Comparative Example 5, and the 45°C cycle thickness expansion rate and 60°C storage thickness expansion rate are lower than those of Example 4, Comparative Example 1 and Comparative Example 5. It can be seen that when the cyclic carbonate compound described in the present application is further added to the electrolyte, a more stable SEI film can be formed, thereby further improving the high-temperature cycle and high-temperature storage performance of the lithium-ion battery, and similar effects can be achieved regardless of whether a single type of cyclic carbonate compound or multiple cyclic carbonate compounds are used.
[0110] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of disclosure involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features without departing from the above disclosed concept. For example, the above features are replaced with the technical features with similar functions disclosed in this application (but not limited to) by each other to form a technical solution.
[0111] Although the subject matter has been described in language specific to structural features and / or methodological logical actions, it should be understood that the subject matter defined in the appended claims is not necessarily limited to the specific features or actions described above. On the contrary, the specific features and actions described above are merely example forms of implementing the claims.
Claims
1. An electrolyte, characterized in that: include: A compound of formula I; , wherein A is selected from -C(=O)- or -S(=O)2-; R1 is selected from substituted or unsubstituted C1 to C 20 alkyl or heteroalkyl, substituted or unsubstituted C1 to C 20 alkoxy or heteroalkoxy, substituted or unsubstituted C6 to C 20 aryl or heteroaryl, substituted or unsubstituted C3 to C 20 alicyclic hydrocarbon group, substituted or unsubstituted C2 to C 20 Any one of the heterocyclic groups, wherein, when substituted, the substituent is halogen; R2, R3 and R4 are each independently selected from hydrogen, halogen, substituted or unsubstituted C1 to C 20 alkyl or heteroalkyl, substituted or unsubstituted C1 to C 20 alkoxy or heteroalkoxy, substituted or unsubstituted C2 to C 20 alkenyl or heteroalkenyl, substituted or unsubstituted C2 to C 20 alkynyl or heteroalkynyl, substituted or unsubstituted C6 to C 20 aryl or heteroaryl, substituted or unsubstituted C3 to C 20 alicyclic hydrocarbon group, substituted or unsubstituted C2 to C 20 Any of the heterocyclic groups, wherein, when substituted, the substituent is halogen; When containing heteroatoms, the heteroatoms include at least one of O, N, P, S, Si or B; n is selected from 1; m is selected from 1.
2. The electrolyte according to claim 1, characterized in that The R1 is selected from substituted or unsubstituted C1 to C 10 alkyl or heteroalkyl, substituted or unsubstituted C1 to C 10 alkoxy or heteroalkoxy, substituted or unsubstituted C6 to C 10 aryl or heteroaryl, substituted or unsubstituted C3 to C 10 alicyclic hydrocarbon group, substituted or unsubstituted C2 to C 10 Any one of the heterocyclic groups; R2, R3 and R4 are each independently selected from hydrogen, halogen, substituted or unsubstituted C1 to C 10 alkyl or heteroalkyl, substituted or unsubstituted C1 to C 10 alkoxy or heteroalkoxy, substituted or unsubstituted C2 to C 10 alkenyl or heteroalkenyl, substituted or unsubstituted C2 to C 10 alkynyl or heteroalkynyl, substituted or unsubstituted C6 to C 10 aryl or heteroaryl, substituted or unsubstituted C3 to C 10 alicyclic hydrocarbon group, substituted or unsubstituted C2 to C 10 Any of the heterocyclic groups.
3. The electrolyte according to claim 1, wherein the compound of formula I comprises at least one of the following compounds: 。 4. The electrolyte according to claim 1, characterized in that Based on the mass of the electrolyte, the mass percentage of the compound of formula I is 0.01% to 5%.
5. The electrolyte according to claim 1, characterized in that The electrolyte further comprises a sulfur-oxygen double bond compound, wherein the sulfur-oxygen double bond compound comprises at least one of the compounds represented by formula (II-A) and formula (II-B); , In formula (II-A) and formula (II-B), R 21 , R 22 , R 23 and R 24 are each independently selected from substituted or unsubstituted C1 to C5 alkyl, substituted or unsubstituted C2 to C 10 alkenyl, substituted or unsubstituted C2 to C 10 Alkynyl, substituted or unsubstituted C3 to C 10 Alicyclic hydrocarbon group, substituted or unsubstituted C6 to C 10 any one of an aryl group, a substituted or unsubstituted C1 to C6 heteroatom-containing group, and, when substituted, the substituent comprises at least one of a halogen and a heteroatom-containing group, wherein the heteroatom comprises at least one of O, S, P, N, Si or B, wherein R 21 and R 22 Bonded to form a ring structure, R 23 and R 24 bonded to form a ring structure.
6. The electrolyte according to claim 5, characterized in that The sulfur-oxygen double bond-containing compound includes at least one of the compounds represented by formula (II-1) to formula (II-20); 。 7. The electrolyte according to claim 5, characterized in that Based on the mass of the electrolyte, the mass percentage of the sulfur-oxygen double bond compound is 0.01% to 5%.
8. The electrolyte according to claim 1, characterized in that The electrolyte further comprises a polynitrile compound; the polynitrile compound comprises at least one of the compounds represented by formula III; , In Formula III, R 31 , R 32 , R 33 , R 34 are each independently selected from hydrogen, substituted or unsubstituted C1 to C 10 Alkyl, substituted or unsubstituted -(CH2) a -CN, substituted or unsubstituted -(CH2) b -O-(CH2) c -CN, substituted or unsubstituted -(CH2) d -CH=CH-(CH2) k -CN, substituted or unsubstituted , substituted or unsubstituted , any one of substituted or unsubstituted alkoxycarbonyl, wherein a, b, c, d, e, f, g, h, i, j, k are each independently selected from integers from 0 to 10, and, when substituted, the substituent includes at least one of halogen; x is selected from an integer from 0 to 3, and, when x is selected from an integer from 1 to 3, R 31 , R 32 , R 33 , R 34 At least two of them are groups containing a cyano group, when x is selected from 0, R 32 and R 34 All contain at least a cyano group.
9. The electrolyte according to claim 8, characterized in that The polynitrile compound includes at least one of the compounds represented by formula III-1 to formula III-18; 。 10. The electrolyte according to claim 8, characterized in that Based on the mass of the electrolyte, the mass percentage of the polynitrile compound is 0.5% to 10%.
11. The electrolyte according to claim 1, characterized in that The electrolyte further comprises a cyclic carbonate compound; the cyclic carbonate compound comprises at least one of the compounds represented by formula IV-A or IV-B; , R 41 and R 42 Each is independently selected from any one of hydrogen, halogen, C1 to C5 alkyl which may be substituted with or without fluorine, and C2 to C5 alkenyl; R 43 , R 44 are each independently selected from any one of hydrogen, halogen and fluorine-substituted C1 to C5 alkyl, C2 to C5 alkenyl, provided that R 43 and R 44 At least one of them is selected from halogen, fluorine-substituted C1 to C5 alkyl or C2 to C5 alkenyl.
12. The electrolyte according to claim 11, characterized in that: The cyclic carbonate compound comprises at least one of the compounds represented by Formula IV-1 to Formula IV-7; 。 13. The electrolyte according to claim 11, characterized in that Based on the mass of the electrolyte, the mass percentage of the cyclic carbonate compound is 0.01% to 5%.
14. An electrochemical device, characterized in that: Comprising the electrolyte according to any one of claims 1 to 13.
15. An electronic device, characterized in that: Comprising the electrochemical device as claimed in claim 14.
Citation Information
Patent Citations
Nonaqueous electrolyte battery and nonaqueous electrolyte, and battery pack, electronic appliance
CN102738501A
Electrolyte and battery
CN109103489A
Nonaqueous electrolyte and nonaqueous electrolyte battery including the same
JP2013232298A